2012
DOI: 10.5551/jat.13482
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Smooth Muscle Cell Alterations Triggered by Mice Adipocytes: Role of High-Fat Diet

Abstract: Aim: Inherent mechanisms leading to vascular smooth muscle cells (VSMC) alterations in obesitylinked type 2 diabetes (T2D) situation remain to be clarified. This study evaluates the impact of supernatant of adipocytes extracted from mice fed high-fat-diets (HFD) on the proliferation and apoptosis of VSMC. Methods: Adipocytes were extracted from visceral white fat pads of male and female C57Bl6 mice showing different stages of metabolic alterations after 20 weeks of vegetal or animal HFD feeding. These cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…In order to evaluate the impact of diet on abdominal white adipose tissue cell contents and aspects were characterized. Mature adipocytes were hypertrophic and hyperplasic in HFD groups compared to control [9,12]. However, the number of non-adipose cells isolated per mg of adipose tissue was comparable in all mice group (Figure 1(a)).…”
Section: Characteristics Of Adipose Tissue From Mice Fed With the Thrmentioning
confidence: 90%
See 1 more Smart Citation
“…In order to evaluate the impact of diet on abdominal white adipose tissue cell contents and aspects were characterized. Mature adipocytes were hypertrophic and hyperplasic in HFD groups compared to control [9,12]. However, the number of non-adipose cells isolated per mg of adipose tissue was comparable in all mice group (Figure 1(a)).…”
Section: Characteristics Of Adipose Tissue From Mice Fed With the Thrmentioning
confidence: 90%
“…Abdominal visceral white adipose tissue was extracted, washed and minced in low glucose Dulbecco's Modified Eagle's Medium (DMEM), then digested in a 1 mg/ml type I collagenase solution (GIBCO) for 45 minutes at 37˚C in a shaking water bath. Afterwards, adipocytes and nonadipose cells were separated by centrifugation and the resulting upper layer (containing the adipose cells) was collected and immediately plated in DMEM [12]. The remaining pellet, containing non-adipose cells, was digested for an additional 20 minutes in a 1 mg/ml type I collagenase solution in a 37˚C water bath under constant shaking.…”
Section: Isolation Of Ascmentioning
confidence: 99%
“…Excess lipid induces insulin resistance in the microvasculature of skeletal muscle and cardiac muscle in humans [31] by reducing insulin’s effects on both microvascular blood flow and volume. In one study, adipocytes from mice fed a high fat diet were shown to alter vascular smooth muscle proliferation and cell mortality [32], this may be particularly important when perivascular fat is considered [33]. Various trans fatty acids have been shown to increase superoxide production and induced inflammation [34], as well as impairment of endothelial insulin signaling and NO production in human endothelial cells.…”
Section: Insulin In the Healthy Vasculaturementioning
confidence: 99%
“…Various trans fatty acids have been shown to increase superoxide production and induced inflammation [34], as well as impairment of endothelial insulin signaling and NO production in human endothelial cells. While in vitro results have not yet been translated into a physiological situation, diet may have both direct effects on vascular function [34], as well as indirect effects through adjacent tissues such as adipocytes [32]. …”
Section: Insulin In the Healthy Vasculaturementioning
confidence: 99%
“…There have been many studies investigating insulin signaling cascades in skeletal muscle [13][14][15] and a variety of other cell types [16,17], and both receptor defects and post-receptor signaling defects have been observed [18] yet insulin must get to the cells before it can engage the receptors, and relies on a functioning microvasculature for access. In the vasculature both endothelial [19][20][21] and vascular smooth muscle cells [22] have shown insulin signaling defects, and functional vascular impairments are also evident. In healthy individuals insulin signaling in the endothelium can increase perfusion of muscle, improving the delivery of nutrients and hormones to muscle [23].…”
Section: Exercise As Treatment For Diabetesmentioning
confidence: 99%